Thermoelectric energy conversion and topological materials based on heavy metal chalcogenides - Roychowdhury, Subhajit; Samanta, Manisha; Banik, Ananya; Biswas, Kanishka (Journal of solid state chemistry, 2019)
The discovery of topological insulators with unique metallic surface states has added a new dimension in the field of electronics and spintronics. Following the initial breakthrough, the topologically non-trivial materials have been extended to various categories namely weak topological insulator, topological crystalline insulator, Dirac semimetal and Weyl semimetal. Interestingly, most of the topological materials are also good candidates for thermoelectric energy conversion because both demand similar material features such as heavy constituent elements, narrow band gap, and high spin-orbit coupling. Heavy metal chalcogenides satisfy these criteria and present a nice platform for exploring both thermoelectrics and topological insulation. Here, we present a brief overview of both topological materials and thermoelectrics with examples based on heavy metal chalcogenides from the perception of a solid-state chemist. Last part of this review deals with the major challenges at the intersection of these two fields and possible solutions to establish the strong correlation between topological and thermoelectric materials. [Display omitted] •Topological and thermoelectric materials demand heavy constituent elements, narrow bandgap and strong spin-orbit coupling.•Overview of both topological material and thermoelectrics based on heavy metal chalcogenides is discussed.•Thermoelectric properties of various topological materials such as TI, WTI, TCI and WSM are discussed.